Penerapan Program Muthola'ah Wajib terhadap Peningkatan Literasi Santri di Pondok Pesantren Fathul Mu'in Ali Masykur Wonosobo - Irfan Syarif Nur Hidayat; Robingun Suyud El Syam; Ahmad Zuhdi (Reflection : Islamic Education Journal, 2025)
This study aims to analyze the implementation of the mandatory muthola'ah program at the Fatkhul Mu'in Ali Masykur Wonosobo Islamic Boarding School, and its contribution to improving students' literacy. This study uses a descriptive qualitative approach with a case study method. Data were collected through direct observation, in-depth interviews with caregivers, educators, boarding school administrators, and students, as well as documentation. Triangulation techniques were used to ensure data validity. The results of the study indicate that the mandatory muthola'ah program implemented in a structured manner every night for 45 minutes is able to build disciplined and independent learning habits. Through this program, students are accustomed to reading yellow books, writing summaries, discussing in groups, and expressing opinions logically. The implementation of this program is also supported by the vision of the boarding school, and intensive mentoring from the administrators. This program contributes significantly to improving students' literacy both academically and in character. The study highlights some students who are less motivated, have difficulty reading Arabic texts, and are afraid of making mistakes during discussions. Patient and consistent coaching indicates that these obstacles can slowly be overcome.